P538 Vedolizumab is effective in real life paediatric inflammatory bowel disease: report from the prospective, multi-centre VEDOKIDS cohort study. (25th January 2019) - Shavit-Brunschwig, Z; Ledder, O; Focht, G; Urlep, D; Lev-Tzion, R; Marcus, D; Broide, E; Assa, A; Hussey, S; Yerushalmy-Feler, A; Levine, A; Markowitz, J; et al.
Abstract: Background: Vedolizumab (VDZ) has proven to be effective in adults, both in Crohn's disease (CD) and ulcerative colitis (UC). Limited data are available in children and none are prospective. We evaluated the short- and mid-term effectiveness and safety of the drug in an interim analysis of the prospective, multi-centre VEDOKIDS cohort study of children with IBD who commenced VDZ. Methods: Although children were managed according to the discretion of the local physician, the study protocol recommended standardised management including VDZ dose of 177 mg/BSA up to 300 mg. Explicit demographic, clinical and safety data were recorded via a REDcap electronic eCRF at weeks 0, 14 and 30. Clinical remission was defined as steroid and EEN-free remission (ie, wPCDAI < 12.5 or PUCAI < 10) without the need for new medications or surgical interventions. Complete remission was defined as clinical remission with CRP < 0.5 mg/dl and ESR < 20 mm/h. Results: Forty-three children were enrolled, 23 (53%) with CD, and 20 (47%) with UC/IBDU (14 (33%) males, 35 (81%) failed previous anti-TNF, median disease duration 2.3 years (IQR 1.2–5.0)). Four children (9%) discontinued the drug due to primary or secondary non-response and their data were imputed for ITT analysis using the blended non-response imputation and LOCF approach for continuous data. Clinical remission rates at Weeks 14 and 30 were 35% and 30% for CD, and 45% and 45% for UC, respectively. The sustained clinical remission rates (at both Weeks 14 and 30) were 22% in CD and 40% in UC ( p = 0.19). Complete remission at Week 30 was noted in 3 children (13%) in the CD group and 4 (20%) in the UC/IBD-U group ( p = 0.42). In the CD Group 19 children (83%) had elevated CRP and/or ESR at week 0, of whom 11% and 5% normalised both markers at Weeks 14 and 30, respectively. In the UC/IBD-U group, 10 (50%) had elevated CRP and/or ESR at baseline, of whom, 40% and 30% normalised the markers at Week 14 and 30, respectively. In the CD group, the mean height z-score improved slightly from −1.17 at baseline to −0.95 at Week 30, but this was not significant ( p = 0.297). Eighteen adverse events (AE) were recorded in 14 children. The 5 AEs graded as possibly related to VDZ were mild–moderate and included back pain, parotitis, myalgia and upper respiratory infection and leukocytoclastic vasculitis; only the latter led to discontinuation of VDZ. There were 5 serious AEs, none likely related to VDZ. Conclusions: In this prospective cohort study, VDZ was safe and effective in a refractory cohort of paediatric IBD. VDZ was numerically more effective in UC/IBD-U than in CD in children, both at Week 14 and Week 30, across all outcomes. This study is supported by grants from ECCO and ESPGHAN.